2020
DOI: 10.31878/ijcrpp.2020.43.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gayatri Mantra Chanting on Attention, Memory, Anxiety and Mental State in Young Athletes: A Prospective Study

Abstract: Introduction: The Gayatri Mantra (GM) is one of the oldest available divine hymns in ancient vedic literature, a mantra of physical, emotional, mental healing and spiritual awakening or self-realization. GM is a standard, validated, empowerment tool aiding in effective behavioral changes leading to optimal and healthy lifestyle. Effect of vedic chanting on consciousness and mental state has been long researched and has been documented in ancient religious literatures. However, due to its religious conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…10 It is contemplated that each of these mantras has medico-spiritual benefits and this has been demonstrated by various studies. 11,[20][21][22][23][24] However, most of these studies conducted on school students. These studies has shown that mantra chanting improves memory, attention, concentration, learning power, 11,20,21 enhance the workplace well-being, 22 enhances the stability of cardiac function by modulating autonomic functions, 23,24 reduce anger and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 It is contemplated that each of these mantras has medico-spiritual benefits and this has been demonstrated by various studies. 11,[20][21][22][23][24] However, most of these studies conducted on school students. These studies has shown that mantra chanting improves memory, attention, concentration, learning power, 11,20,21 enhance the workplace well-being, 22 enhances the stability of cardiac function by modulating autonomic functions, 23,24 reduce anger and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…11,[20][21][22][23][24] However, most of these studies conducted on school students. These studies has shown that mantra chanting improves memory, attention, concentration, learning power, 11,20,21 enhance the workplace well-being, 22 enhances the stability of cardiac function by modulating autonomic functions, 23,24 reduce anger and anxiety. 25 Reaction time is an important skill required in all profession, however it has a greater value among drivers, as the increased reaction time is correlated to increased number of road traffic accidents.…”
Section: Discussionmentioning
confidence: 99%
“…There is a good amount of traditional literature which mentions the effects of chanting Gayatri mantras (GM) on consciousness and mental state of the person (Samajdar et al, 2020). But owing to its religious connotations, conceptual or theoretical explanations, its scientific scrutiny and validation has not been popularized.…”
Section: Need Of the Studymentioning
confidence: 99%
“…Recent research also indicates that Pranayama (breathwork) is helpful in managing stress and anxiety in several populations [34][35][36]. The literature suggests that mantra is an effective practice for managing stress and anxiety [37][38][39][40]. Research indicates that those who engage in reflection during a stressful experience are more resilient and have better well-being [41].…”
Section: Spiritual Growth and Development (Sgandd)mentioning
confidence: 99%